Test Data Analysis on Voltage Regulation of Proportion Relief Valve - Pei Weichi; Cao Fukai; Zhao Shuzhong (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
The miniature reform design was to improve the voltage regulation of regular valve and proportional valve. LabVIEW was used to develop CAT voltage regulation of proportion relief valve with electro hydraulic proportional control and visual instrument. The content of the pressure adjustment of proportional relief valve was introduced from different angles and the steady-state. Test on voltage regulation of proportion relief valve was analyzed. The sampling data were processed and analyzed on a time domain and frequency domain basis. Related conclusions are made by analysis on current linearity, steady-state pressure, and pressure-adjusting delay. Systematic methods and references are provided for the development of other valves to improve the function and the system of proportional valve. DOI: http://dx.doi.org/10.11591/telkomnika.v12i6.5488